Innovation in Islamic finance the way forward - Hasan, Aznan (2013)
This paper attempts at exploring the process of innovation in modern Islamic finance. It argues that although the practice of replication is working well as far as the Islamic finance industry is concerned, the long term practice will harm the industry. Hence the paper proposes that a paradigm shift is needed in the innovation process, to ensure not only Shariah compliant of the products to be innovated, but also its viability and resilient in facing the challenging world of finance